Pentazocine Misuse among Sickle Cell Disease Patients and The Role of Lack of Enforcement of Opioid Dispensing Regulations by Community Pharmacies: A Descriptive Observational Study - Oluomachi Charity Nnachi; Chinedu Obasi Akpa; Favour Ogonna Nwani; Oghenevwogaga Obukohwo Edenya (Advances in Public Health)
Introduction. Sickle cell disease (SCD) is a chronic disease characterized by debilitating bone pains which commonly necessitate the use of analgesic drugs including opioids and psychotropic substances such as pentazocine which are controlled medicines in Nigeria. Opioid misuse including dependence and addiction is an increasing trend among SCD patients, and it has serious adverse implications on their social, economic, and physical well-being. The role of lack of implementation of existent regulation on the dispensing of opioids by pharmacies has not been adequately investigated. Objective. The primary objective of this study is to define the sociodemographic and clinical implications of pentazocine misuse among patients with SCD and to describe the contributions of lack of enforcement of opioid dispensing regulations to this menace. Materials and Methods. The study was a descriptive observational study. A 29-item pretested and prevalidated questionnaire was administered to 21 SCD patients with an established history of pentazocine misuse and addiction to establish their demographics, details of opioid use, and their clinical effects. Nine community pharmacies were interviewed to ascertain their knowledge of controlled medicines and their compliance to existent regulations on the dispensation of opioids. Results. The median (interquartile range) age of the SCD subjects was 24 years. The majority of subjects (14, 66.7%) had tertiary education. Fifteen (71.4%) of them had a history of pentazocine misuse for over two years. All subjects source pentazocine injection from local pharmacies and patent medicine shops without prescription, while 19.0% get home deliveries. Seventeen (80.9%) of the SCD subjects desired to discontinue the habit; however, inadequate medical support was reported to contribute to their inability to overcome this practice in 14 (54.3%) patients. Most of the local pharmacies/drug shop proprietors are aware of drug laws guiding controlled medicines in Nigeria. However, about 77.9% of pharmacies interviewed retail pentazocine without prescription. A lack of enforcement by the state and federal taskforce was reported to contribute to this practice. Conclusion. Pentazocine misuse is a serious problem in patients with SCD. Inadequate medical support and lack of enforcement of regulations on dispensing opioids by community pharmacies are contributors to this menace.